Architecture and design of an embeddable system for SCAN-based compression, encryption and information hiding - Chrysos, Grigorios; Dollas, Apostolos; Bourbakis, Nikolaos (Journal of real-time image processing, 2007)
The SCAN formal languages can be used for tight integration of image and video compression, encryption and data hiding. This work presents such a tightly integrated embeddable system, which can be used as a “black box” in streaming media. In our previous work we had studied and implemented separate modules for SCAN compression and SCAN encryption, using a large Virtex II FPGA for each. There were no implementation of data hiding, no integration of the three aspects of SCAN, and no complete design for decompression/decryption/unhiding. This paper presents a new architecture and a complete design for SCAN compression/encryption/hiding, as well as the corresponding decompression/decryption/data unhiding operations. A recent technology based on an embedded processor with reconfigurable fabric extensions has been used for this design, which was carried out to post place and route cycle-accurate simulations with real video sequences. The new design is of substantially lower performance versus the previous reconfigurable implementations of single modules, however, it proves that a low-cost embeddable system can be made for all three operations. This paper presents in detail the different aspects of the architecture, their integration, and their mapping to the fixed and reconfigurable resources of the Stretch S5000 reconfigurable processor. To our knowledge, this is the first tightly integrated compression/encryption/ information hiding system to be reported in the literature.